Analysis of Claims for Acute Ischemic Stroke Patients with National Health Insurance (JKN) Financing at the University of Indonesia Hospital in 2024 - Gemia Clarisa Fathi; Purnawan Junadi (International Journal Labs, 2025)
Acute ischemic stroke is a leading cause of mortality and disability in Indonesia, with thrombolysis therapy using alteplase being a high-cost treatment. The gap between the INA-CBGs tariff and actual hospital costs, particularly for ischemic stroke, poses a significant challenge to health financing efficiency. This study aims to analyze the disparity between INA-CBGs rates and actual costs for treating acute ischemic stroke at the University of Indonesia Hospital (RSUI). Using a retrospective descriptive design, the study examines JKN claim data from January to December 2024, with a sample of 340 claims of ischemic stroke patients (ICD-10 code I63.9) in the INA-CBGs G-4-14 group. The analysis includes patient characteristics, treatment class, severity level, and cost components. Results show that the majority of patients were male (57.4%) and aged 60–74 years (46.5%). Most patients (90.3%) did not receive thrombolysis, with moderate severity being the most common case (66.8%). A significant discrepancy was found between the INA-CBGs tariff (IDR 2,716,782,600) and actual hospital costs (IDR 3,468,927,095), with a negative difference of 27.7%. The main cost components were medicines (22.5%), followed by room accommodation, radiology, and laboratories. The study highlights the need for policy evaluation to address the financing gap in stroke services to ensure equitable and sustainable health financing.